Mighty Microbes - Noor Effendy, Muhamad Fadly Shah; Tham, May Ling; Tam, Xi Yuan; Rozilah, Megat Mohamad Irfan; Chew, Han Hoong; Saad, Wan Zuhainis (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Gamification is used for students engagement, motivation, pique curiosity and instill interest. Once they are engage, highly motivated, they will learn. The Mighty Microbes are designed to engage learners in a form of game cards with augmented reality that facilitate learners in enhancing the understanding about microbes and their importance in daily lives.